Periodic variations of phosphorus migration and transformation in a eutrophic lake of China: The role of algae bloom and collapse - Han, Chaonan; Tang, Yu; Wu, Hao; Sun, Ningning; Dai, Yan; Dai, Tianhao (Frontiers in Earth Science, 2023)
It is a two-way interaction between algae bloom events and nutrient cycles in aquatic environments. In Meiliang bay of Taihu Lake, phosphorus (P) forms in the water, sediment and pore water, and bacterial community structures in the sediment were investigated in June 2021 (the algae bloom period) and December 2021 (the algae collapse period). The aim of this study is to clarify the periodic variations of P migration and transformation driven by algae bloom and collapse. Results showed that concentrations of total P and total particulate P in the water during the algae bloom period (0.13~0.25 mg/L) were much higher than those during the algae collapse period (0~0.13 mg/L), which was mainly caused by the uptake of phosphate (PO43-) by algae in the surface water. Compared with the algae bloom period, there were higher concentrations of organic P (OP), iron-bound P (FeP) and inorganic P in the sediments during the algae collapse period. The propositions of OP and FeP in total P in the sediments increased from 19% and 17% during the algae bloom period to 27% and 33% during the algae collapse period. These suggest the cumulative trend of OP and FeP in the sediments during the algae collapse period, and FeP might be formed through the processes of OP mineralization and P adsorption by iron oxides/hydroxides in the sediments. Different routes of sediment P regeneration existed over the two periods. During the algae bloom period, the similar vertical variations of labile PO43- and labile Fe2+ in the sediments provided in situ, high-resolution evidence for FeP reductive dissolution driven by FRBs activities. During the algae collapse period, OP mineralization driven by organic P-solubilizing bacteria activities and accelerated by the sulfate reduction process was confirmed by the similar vertical variations of labile PO43- and labile S2- in the sediments. Therefore, treatment approaches and management practices should consider the periodic variations of internal P cycles in aquatic environments during the algae bloom and algae collapse periods to avoid inefficient treatments of lake eutrophication and algae bloom.